Hypothalamus–Muscle Parallel Induction of Metabolic Pathways Following Physical Exercise - Katz, Almog; Gonen, Meital; Shahar, Yael; Roichman, Asael; Lerrer, Batia; Cohen, Haim Yosef (Frontiers in Neuroscience, 2022)
The modern lifestyle requires less physical activity and skills during our daily routine, leading to multiple pathologies related to physical disabilities and energy accessibility. Thus, exploring the mechanisms underlying the metabolic regulation of exercise is crucial. Here, we characterized the effect of endurance forced and voluntary exercise on three key metabolic signaling pathways, sirtuins, AMPK and mTOR, across several metabolic tissues: brain, muscles and liver. Both voluntary and forced exercises induced AMPK with higher intensity in the first. The comparison between those metabolic tissues revealed that the hypothalamus and the hippocampus, two brain parts, showed different metabolic signaling activities. Strikingly, despite the major differences in the physiology of muscle and hypothalamic tissues, the hypothalamus replicates the metabolic response of the muscle in response to physical exercise. Specifically, muscle and hypothalamic tissues showed an increase and a decrease of AMPK and mTOR signaling, respectively. Overall, this study reveals a new insight about the relation between the hypothalamus and muscle, which enhances the coordination within the muscle-brain axis and potentially improves the systemic response to physical activity performance, promoting health inactivity disorders.